2021
DOI: 10.1177/09732586211060010
|View full text |Cite
|
Sign up to set email alerts
|

Does Online Dating Promotion Vary Across Cultures? A Cross-cultural Analysis of Homepage Advertisements of Online Dating Services in 51 Countries

Abstract: This study extends our understanding of the influence of culture on advertising within the novel context of online dating. People around the world have come to depend on online dating services (ODSs) to participate in the dating process. Since the norms and expectations of dating are influenced by a country’s cultural values, we expect ODSs to adapt their advertising messages to be congruent with these values. Using the Pollay–Hofstede framework, we examine the relationship between advertising appeals used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Interestingly, psychosocial motivations like casual sex and one-night stands did not emerge as significant themes in the factor analysis. This finding underscores the influence of cultural differences [ 28 , 34 ] on online dating behaviours. According to Ref.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Interestingly, psychosocial motivations like casual sex and one-night stands did not emerge as significant themes in the factor analysis. This finding underscores the influence of cultural differences [ 28 , 34 ] on online dating behaviours. According to Ref.…”
Section: Discussionsupporting
confidence: 54%
“…found that those users who sought to gratify their physical needs met their dating partners and had casual sex more frequently than those who were not motivated to use dating apps for physical gratification. However, results from collectivistic and Asian countries paint a slightly different picture of the motivations and outcomes of dating app usage [ 28 ]. Prior research in China, Japan, and Korea has shown that people use dating apps mainly for relationship-seeking and socialisation motivations [ 36 ];[ 89 ].…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individualism and collectivism cultures can influence user perceptions and behaviors towards online dating [42]. In a country characterized by a collectivistic culture, the nature of such cultures tends to favor shared activities, such as livestreaming, over solitary ones [36][37][38].…”
Section: Voice-based Mda In Chinamentioning
confidence: 99%